CLOTHING MODELS’ FASHION SHOWS OF THE UKRAINE SEWING ENTERPRISES IN 1940–1960s - Костогриз, Ю. О.; Герасименко, О. Д.; Шмагало, Р. Т.; Пашкевич, К. Л. (Art and Design, 2020)
The purpose to investigate the peculiarities of the development of fashion shows of the 1940-1960s in Ukraine based on archival materials. Methodology. In the recearce of materials and visual sources historical, visual-analytical methods, art-compositional analysis of products were used. Results. On the basis of archival materials, the demonstrations of clothing models that took place at the sewing and profile enterprises of light industry of Ukraine from the mid-1940s to the end of the 1960s were studied. An artistic and compositional analysis of clothing models, which were demonstrated at fashion shows, was carried out. Samples of models of men’s, women’s and children’s clothes made by the sewing enterprises of the USSR in the specified years are resulted. The analysis of clothing models is performed in order to determine the main fashion trends in the period under study. An overview of the plots of film periodicals of the 1940–1960s is given, in which the finished products of light industry. The formation and development of fashion shows for adults and children at sewing and specialized enterprises of Ukraine in the 1940–1960s of the twentieth century on the basis of the study of archival materials is considered. Practical significance. The collected materials and their analysis made it possible to trace the formation of fashion shows at the sewing enterprises of the Ukrainian SSR in the 1940–1960s and provide a compositional-constructive analysis of clothing models. The results can be used in teaching disciplines related to the history of costume and fashion, as well as in further scientific research.